A new recombinant protein expression system for high-throughput screening in the yeast Yarrowia lipolytica - Bordes, Florence; Fudalej, Franck; Dossat, Valérie; Nicaud, Jean-Marc; Marty, Alain (Journal of microbiological methods, 2007)
Development of a high-throughput eukaryotic screening procedure is important to increase success in obtaining improved enzymes through directed enzyme evolution. This procedure was developed for the yeast Yarrowia lipolytica which becomes the second eukaryotic host for this purpose. The extracellular lipase Lip2 was used as expressed enzyme but this system will be easily adjusted for other enzymes. We adapted and optimized the protocol for protein expression by Y. lipolytica in 96-well microplates. Yeast transformation efficiency and expression cassette insertion were increased by constructing a strain containing a zeta docking platform for targeted integration into the genome. The coefficient of variance of the full process was reduced from 36.3% to 18.9%. The main part of the variability (11.7%) arises from the specific lipase enzyme assay whereas the coefficient of variance concerning transformation, growth and expression steps represents only 7.2%. The rate of clone with no activity was reduced from 5.8% to 0.2%. Both transformation efficiency and variability are then compatible with high-throughput screening in the yeast Y. lipolytica.